Home-Based Wound Care dan Layanan Online Diponegoro Wound Care: Solusi Penyembuhan Luka untuk Pasien di Masa Pandemi Covid-19 - Niken Safitri Dyan Kusumaningrum; Akhmad Ismail; Andrian Budi Prasetyo (Jurnal Pengabdian Pada Masyarakat, 2021)
HOME-BASED WOUND CARE AND ONLINE SERVICE OF DIPONEGORO WOUND CARE: SOLUTION OF WOUND HEALING FOR PATIENTS DURING PANDEMIC COVID-19. The period of the Covid-19 pandemic caused various impacts both individually and systematically. Those are also including the health system services, where in accessing that services, people tend to dace limitations. Therefore, Diponegoro Wound Care as a wound care service center provides an alternative to patients using home-based wound care method. The home-based wound care and online service provide wound care as well as consultation and education about wounds. Home-based wound care service is carried out at the patient’s home according to the inform consent. Meanwhile, online service is provided through Whatsapp chat application to reach all level of patients. The results of the implementation of home-based wound care and online service concluded that wound care using a home-based care setting was recommended for patients who had wounds with various complications. This is necessary to provide services that improve the quality of life of patients, but tend to be safer for patients because they do not need to come to healthcare service which are still at high risk of experienceing exposure to Covid-19 virus during this pandemic.